Proteomic Profiling of Purified Rabies Virus Particles - Zhang, Yan (Virol Sin, 2019)
While host proteins incorporated into virions during viral budding from infected cell are known to play essential roles in multiple process of the life cycle of progeny virus, these characteristics have been largely neglected in studies on rabies virus (RABV). Here, we purified the RABV virions with good purity and integrity, and analyzed their proteome by nano LC–MS/MS, followed by the confirmation with immunoblot and immuno-electronic microscopy. In addition to the 5 viral proteins, 49 cellular proteins were reproducibly identified to be incorporated into matured RABV virions. Function annotation suggested that 24 of them were likely involved in virus replication. Furthermore, cryo-EM was employed to observe the purified RABV virions, generating high-resolution pictures of the bullet-shaped virion structure of RABV. This study has provided new insights into the host proteins composition in RABV virion and shed the light for further investigation on molecular mechanisms of RABV infection, as well as the discovery of new anti-RABV therapeutics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12250-019-00157-6) contains supplementary material, which is available to authorized users.